Preparation method of anti-ultraviolet antibacterial multifunctional polyester fiber

Through the combined melt extrusion process of white polyester slices and functional slices, combined with the online monitoring system, the preparation of UV-resistant and antibacterial multifunctional polyester fibers has been solved, and the problems of single functions and insufficient performance of the existing spinning functional fiber preparation methods have been achieved, achieving uniformity and versatility of product quality.

CN119877122APending Publication Date: 2025-04-25ZHEJIANG GUXIANDAO POLYESTER DOPE DYED YARN CO LTD +2

Patent Information

Application Number
CN202510000026.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-08-11
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing method of preparing spinning functional fibers has the problem of single implementation methods and few functions, and the heat resistance and pressure resistance of some masterbatches are poor, making it difficult to achieve better results through a single form.

Method used

White polyester slices and the first functional slices are used as the main material and the second functional slices are auxiliary material. Through the combined melt extrusion process of the mixing silo and the main screw, combined with the online monitoring system, the preparation of multifunctional polyester fiber is realized.

Benefits of technology

The uniformity and versatility of product quality are achieved, and a variety of functional fibers can be flexiblely produced according to the amount and state of the addition of different second functional slices, avoiding melt pressure fluctuations and improving the performance of the fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877122A_ABST
    Figure CN119877122A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an anti-ultraviolet antibacterial multifunctional polyester fiber, and belongs to the technical field of melt spinning. White polyester chips are fed into a mixing bin through a main bin, a first functional chip is fed into the mixing bin through a first distribution bin, a second functional chip is fed into a small screw through a second distribution bin, the first functional chip is nano TiO2, the second functional chip is a nano silver antibacterial agent, melt extrusion and spinning are performed, the breaking strength of the obtained uvioresistant and antibacterial functional polyester fiber is 84.4 N, the breaking strength is 7.6 cN / dtex, and the uvioresistant and antibacterial functional polyester fiber is obtained. The dry heat shrinkage rate is 6.0%, and the elongation at break is 15.9%; the anti-ultraviolet performance is high, and the breaking strength retention rate is 90% or above; the bacterial activity value is less than-1.0, and no fungus is bred. A signal feedback device for detecting the aging strength retention rate and the silver ion content is arranged before the packaging process, and the adding speed and the adding amount of the first function slice and the second function slice are controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for preparing UV-resistant and antibacterial multifunctional polyester fiber, and belongs to the technical field of melt spinning. Background Art

[0002] At present, when spinning functional fibers, white polyester chips are mostly extruded and melted to form a melt, and then the functional components are injected through a small screw (such as CN102787376A), and the functional components are added by melt mixing; or as shown in CN214612856U, white polyester chips are first mixed with functional components and then melt extruded for spinning. Both methods have the defects of a single implementation method and few functions that can be realized; and when some masterbatches have poor heat resistance and pressure resistance, it is difficult to achieve good results through a single form, such as color masterbatches, fluorescent masterbatches, etc., the color pigments and fluorescent components added are mostly organic components, and the heat resistance is usually poor. Summary of the invention

[0003] In view of this, the present application provides a method for preparing an anti-ultraviolet and antibacterial multifunctional polyester fiber, which can timely adjust the addition amount of the front-end functional components to achieve uniformity of product quality.

[0004] Specifically, the present application is implemented in the following ways:

[0005] A method for preparing an anti-ultraviolet and antibacterial multifunctional polyester fiber, with white polyester chips and first functional chips as main materials, and second functional chips as auxiliary materials, the white polyester chips are supplied to a main material bin, and the first functional chips are supplied to a sub-bin, the two are mixed in a mixing bin and then fed into a main screw for melt extrusion to form a melt, while the second functional chips are extruded by a small screw to form a melt, which is mixed with the extruded melt of the main screw and fed into a spinning process, and control systems are arranged between the mixing bin and the main material bin, between the mixing bin and the sub-bin, and between the small screw and the main screw, respectively, to perform online monitoring on the extruded melt of the supplied white polyester chips, the first functional chips, and the second functional chips.

[0006] The above process method is mainly based on white polyester chips and first functional chips, supplemented by second functional chips. By adding commonly used white polyester chips and first functional chips and adjusting different second functional chips, polyester fibers with different effects can be processed. In the above process, the amount of white polyester chips and first functional chips added is relatively large, and they are also the two components that have the most significant impact on melt performance in production. The two are first mixed and then dissolved, which can well control the product quality. When a relatively small amount of the second functional chip melt is added, the second component can be added. Due to the above special settings of its addition amount and addition state, its addition will not cause melt pressure fluctuations, thereby realizing flexible production and processing of multiple functions.

[0007] Further, as a preference:

[0008] When the first functional slice is dried by drying mechanism 1 to a water content of ≤0.4%, it is added into the mixing bin, and when the second functional slice is dried by drying mechanism 2 to a water content of ≤0.4%, it is sent into a small screw for extrusion and melting.

[0009] The small screw rod is a single screw rod or a twin screw rod.

[0010] The main screw has four spinning positions, and each spinning position corresponds to a small screw.

[0011] The first functional slice is any one of flame retardant masterbatch, antibacterial masterbatch, anti-ultraviolet masterbatch, fluorescent masterbatch, and color masterbatch; the second functional slice is any one of flame retardant masterbatch, antibacterial masterbatch, anti-ultraviolet masterbatch, fluorescent masterbatch, color masterbatch, and antistatic masterbatch, and the first functional slice is different from the second functional slice.

[0012] A signal feedback device is provided in the spinning process, and the signal feedback device is connected to each control system. Based on the fiber condition, before the fiber package is formed, the signal feedback device monitors the functional indicators online, such as: the flame retardant component can obtain the phosphorus content by monitoring the P element content, the antistatic component can monitor the resistance change to obtain the resistance signal, the antibacterial component can obtain the silver content by monitoring the silver element content, the anti-ultraviolet detection spectrum transmittance change, the color and fluorescence can obtain the color difference signal by online colorimetry, and the corresponding feed amount and feed speed are adjusted.

[0013] Several specific multifunctional polyester fibers are added below.

[0014] The multifunctional polyester fiber is a colored fluorescent functional polyester fiber, the white polyester chips are polyester chips with a characteristic viscosity of 0.85-1.25 dl / g, a moisture content of ≤40 ppm, and a feeding speed of 1.5-15 tons / h; the first functional chips are masterbatches with a moisture content of ≤40 ppm and an addition amount of 2-5% of the mass of the white polyester chips; the screw extrusion temperature is 270-290°C; the second functional chips are fluorescent masterbatches with a characteristic viscosity of 0.3-0.7 dl / g and a moisture content of <0.5%; the small screw extrusion temperature is 238-270°C, the addition amount of the fluorescent masterbatch relative to the white polyester chips is 60-250 ppm, and the stretching ratio is 5.4-6.0.

[0015] The multifunctional polyester fiber is a colored flame-retardant functional polyester fiber, the white polyester slice is a polyester slice with an intrinsic viscosity of 0.85-1.25 dl / g, a moisture content of ≤40 ppm, and a feeding speed of 1.5-30 tons / h; the first functional slice is a flame-retardant masterbatch with a moisture content of ≤40 ppm, an intrinsic viscosity of 0.85-1.25 dl / g, a P element content of 5000-100000 ppm, and a feeding speed of 5kg-3000kg / h; the screw extrusion temperature is 230-320℃; the second functional slice is a masterbatch with a characteristic viscosity of 0.3-0.7dl / g and a moisture content of <0.5%; the small screw extrusion temperature is 240-300℃, the output melt speed is 5kg-3000kg / h, the output melt ratio relative to the main screw is ≤5%, and the injection pressure is greater than the main screw pressure; a signal feedback device for detecting phosphorus content and color difference is set before the winding process of the spinning process to control the addition speed and amount of the first functional masterbatch and the second functional masterbatch.

[0016] The multifunctional polyester fiber is an antistatic fluorescent functional polyester fiber, the white polyester slice is a polyester slice with an intrinsic viscosity of 0.85-1.25dl / g, a moisture content of ≤40ppm, and a feeding speed of 1.5-15 tons / h; the first functional slice is an antistatic masterbatch, with a moisture content of ≤40ppm and a feeding speed of 1kg-1000kg / h; the screw extrusion temperature is 230-320°C; the second functional slice is a fluorescent masterbatch, with an intrinsic viscosity of 0.3-0.7dl / g and a moisture content of <0.5%; the small screw extrusion temperature is 240-300°C, the output melt speed is 5kg-3000kg / h, the output melt ratio relative to the main screw is ≤5%, and the injection pressure is greater than the main screw pressure; a signal feedback device for detecting resistance changes and color difference (or whiteness) is arranged before the winding process of the spinning process to control the adding speed and amount of the first functional masterbatch and the second functional masterbatch.

[0017] The multifunctional polyester fiber is an anti-ultraviolet and antibacterial functional polyester fiber, the white polyester slice is a polyester slice with an intrinsic viscosity of 0.85-1.25dl / g, a moisture content of ≤40ppm, and a feeding speed of 1.5-15 tons / h; the first functional slice is an anti-ultraviolet masterbatch, with a moisture content of ≤40ppm and a feeding speed of 1kg-1000kg / h; the screw extrusion temperature is 230-320°C; the second functional slice is an antibacterial masterbatch, with an intrinsic viscosity of 0.3-0.7dl / g, a silver ion content of 200-8000ppm, and a moisture content of <0.5%; the small screw extrusion temperature is 240-300°C, the output melt speed is 5kg-3000kg / h, the output melt ratio relative to the main screw is ≤5%, and the injection pressure is greater than the main screw pressure; a signal feedback device for detecting spectral transmittance changes and silver content is arranged before the winding process of the spinning process to control the adding speed and amount of the first functional masterbatch and the second functional masterbatch. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic diagram of the process flow of this application.

[0019] Numbers in the figure: 1. Main material bin; 11. First control system; 2. Distribution bin one; 3. Distribution bin two; 4. Mixing bin; 5. Main screw; 6. Drying mechanism one; 61. Second control system; 7. Drying mechanism two; 8. Small screw; 81. Third control system. DETAILED DESCRIPTION

[0020] Example 1

[0021] This example is about preparing 1000D colored flame-retardant functional polyester fiber.

[0022] (1) Raw materials: white polyester chips are polyester chips with an intrinsic viscosity of 1.05 dl / g and a moisture content of 10 ppm; the first functional chips are flame retardant masterbatch (phosphorus flame retardant), with an intrinsic viscosity of 0.95 dl / g and a P element content of 44000 ppm; the second functional chips are color masterbatch (black masterbatch may be used), with an intrinsic viscosity of 0.43 dl / g.

[0023] (2) Feeding: Combined Figure 1 The white polyester chips are fed into the mixing bin 4 through the main bin 1, and the feeding speed of the white polyester chips is 83kg / h; the first functional chips are fed into the mixing bin 4 through the sub-bin 1 2, and the feeding amount is 12.26kg; the second functional chips are fed into the small screw 8 through the sub-bin 2 3, and the adding speed is 1.66kg / h.

[0024] (3) Melt extrusion: The mixed material in the mixing bin 4 is fed into the main screw 5. The parameters of the main screw are set as shown in Table 1; the parameters of the small screw 8 are set as shown in Table 2.

[0025] Table 1: Main screw parameters

[0026]

[0027] Table 2: Process parameters of small screw

[0028] .

[0030] (4) Spinning process:

[0031] Spinning colored flame-retardant polyester industrial yarn of 1110dtex / 192f specification, spinneret specification 0.6mm*1.2mm / 192f, 40μm sintered metal mesh filter element.

[0032] W / D: 2600m / min, tension: 100cN, mesh pressure: 2.2bar.

[0033] Metering pump specifications: 20cc / r, metering pump speed: 12.55r / min.

[0034] Slow cooler temperature: 330℃.

[0035] Side wind speed: 0.55m / s, wind temperature: 20℃, humidity: 75%.

[0036] Spinning oil: GXM-100.

[0037] Oil pump specifications: 0.08cc / r, oil pump speed: 45r / min.

[0038] The roller temperature and roller speed were set as shown in Table 3, and the draft ratio was 4.78.

[0039] Table 3: Temperature and speed settings of each spinning winding roller

[0040]

[0041] A signal feedback device for detecting phosphorus content and color difference is set before the winding process: when the phosphorus content exceeds 6500ppm, it indicates that the amount of flame retardant masterbatch added exceeds the standard, and the signal is transmitted to the first control system 11. The first control system 11 increases the feeding speed of white polyester chips accordingly, which is equivalent to reducing the feeding amount of flame retardant masterbatch. On the contrary, when the phosphorus content is lower than 4000ppm, it indicates that the amount of flame retardant masterbatch added is insufficient, then the feeding speed of white polyester chips is reduced or the supply of flame retardant masterbatch is increased; when the RGB value of the fiber exceeds the set value or the fluctuation range exceeds 10%, the addition amount of the second functional masterbatch is adjusted to change the addition amount of the color masterbatch.

[0042] When spinning 1110dtex / 192f specification fibers, the measured fineness is 1125dtex, the breaking strength is 82.12N, the breaking tenacity is 7.30cN / dtex, the dry heat shrinkage is 7.0%, the breaking elongation is 14.5%, the network is 5; the L value is 90, the B value is 4.6, the a value is -1.5, and the phosphorus content in the fiber is 6500ppm.

[0043] Example 1-1

[0044] Common masterbatches are mostly hydrophobic substances, which are prone to static electricity. In order to balance the breaking strength and lint, based on the mechanism that the larger the stretching ratio and the more intense the stretching, the easier it is to obtain strength, but also the easier it is to produce lint, this example selects a stretching ratio of 5.35 to test the effect of the addition amount of masterbatches relative to white polyester chips on the spinning condition.

[0045] After preliminary tests, we determined that the relative addition amount range of a masterbatch with a more prominent influence is 2-3.5%. The following selects 4 addition amount gradients within this range, and calculates the color pump speed (i.e., the metering pump speed of the small screw 8) from low to high for each experiment (other parameter settings are the same as in Example 1), and the results are shown in Table 4.

[0046] Table 4: Effect of different masterbatch addition amounts on the reaction

[0047]

[0048]

[0049] It can be seen from Table 4 that as the amount of masterbatch added relative to white polyester chips increases, the severity of the bundle divergence phenomenon gradually increases, the full roll rate decreases significantly, and the single filament breakage and terry yarn phenomenon increase. Especially after exceeding 3%, there is almost no full roll; when it is below 3%, although there is still a bundle divergence phenomenon, the appearance index is normal, and when it is below 2%, the bundle divergence phenomenon is not obvious. Therefore, it is appropriate to control the amount of masterbatch added to below 3%.

[0050] Example 1-2

[0051] The configuration of this embodiment is the same as that of embodiment 1, except that: two stretching ratios of 5.35 and 5.0 are used as variables, and multiple parallel samples are tested respectively to determine the effect of the stretching ratio on the performance of products of the same specification, as shown in Table 5.

[0052] Table 5: Comparison of fiber performance parameters under different stretching ratios

[0053]

[0054] Combined with Example 1 (stretching ratio 4.78), and compared with Table 5, it can be seen that when processing with the same specifications (the specifications in Table 5 are 1110), the larger the stretching ratio, the higher the actual fineness, the higher the strength, intensity and dry heat shrinkage, and the lower the elongation.

[0055] Example 2

[0056] This example is used to prepare colored fluorescent polyester industrial yarn:

[0057] (1) Raw materials: white polyester chips are polyester chips with an intrinsic viscosity of 1.05 dl / g and a moisture content of 10 ppm; the first functional chips are masterbatches (black masterbatches can be used in this embodiment) with an intrinsic viscosity of 0.43 dl / g, and the addition amount is 3% of the weight of the white polyester chips; the second functional chips are fluorescent masterbatches (whitening agent PS-1 can be used in this embodiment) with an intrinsic viscosity of 0.52 dl / g, and the addition amount is 2% of the weight of the white polyester chips.

[0058] (2) Feeding: Combined Figure 1 The white polyester chips are fed into the mixing bin 4 through the main bin 1, and the feeding speed of the white polyester chips is 83 kg / h; the first functional chips are fed into the mixing bin 4 through the sub-bin 1 2, and the second functional chips are fed into the small screw 8 through the sub-bin 2 3.

[0059] (3) Melt extrusion: The mixed material in the mixing bin 4 is fed into the main screw 5, and the parameters of the main screw are set as shown in Table 6; the parameters of the small screw 8 are set as shown in Table 7, and the corresponding fluorescent masterbatch addition content is 200 ppm.

[0060] Table 6: Main screw parameters

[0061]

[0062] Table 7: Process parameters of small screw

[0063]

[0064] (4) Spinning process:

[0065] Spinning colored fluorescent polyester fiber with specification of 1110dtex / 192f, spinneret specification of 0.6mm*1.2mm / 192f, 40μm sintered metal mesh filter element.

[0066] The roller temperature and roller speed were set as shown in Table 8, and the stretch ratio was 5.9.

[0067] Table 8: Temperature and speed settings of each spinning winding roller

[0068]

[0069]

[0070] A signal feedback device for detecting whiteness and color difference is set before the packaging process: when color difference occurs in the fiber, the signal is transmitted to the first control system 11, and the first control system 11 adjusts the relative feeding speed of the white polyester chips accordingly, that is, changes the relative addition amount of the masterbatch; when the fiber has a brightness coefficient of <0.20 and the luminous intensity is less than 3000 a.u. under ultraviolet light excitation, it indicates that the fluorescent masterbatch is insufficiently added, and the addition speed of the second functional masterbatch can make up for the deficiency; conversely, when the whiteness is higher than the brightness coefficient ≥0.20 and the luminous intensity is greater than 3000 a.u. under ultraviolet light excitation, it indicates that the fluorescent masterbatch is excessively added, and the addition speed of the second functional masterbatch is adjusted to reduce the addition speed of the fluorescent masterbatch.

[0071] The polyester fiber obtained by the above process has a breaking strength of 92.4N, a breaking tenacity of 8.18cN / dtex, a breaking elongation of 12.9%, an L value of 60.44, a B value of -4.92, and an a value of 1.74.

[0072] Example 2-1

[0073] The configuration of this embodiment is the same as that of embodiment 1, except that the amount of fluorescent masterbatch added is different, as shown in Table 9.

[0074] Table 9: Effect of different fluorescent masterbatch addition amounts on fiber properties

[0075]

[0076]

[0077] It can be seen from Table 9 that with the increase of the amount of fluorescent masterbatch added, the change pattern of breaking strength and breaking elongation is not obvious, basically maintaining at about 93-94N for breaking strength, 8.1-8.3cN / dtex for breaking strength, and 12.7-12.9% for breaking elongation. The chromaticity L value decreases significantly, and the fiber becomes darker; the B value decreases, and the fluorescent agent plays a whitening role. Comprehensive consideration: for dark colors, it is suitable to control the amount of fluorescent masterbatch added to 60-200ppm, and for light colors, it is suitable to control the amount of fluorescent masterbatch added to 200-300ppm.

[0078] Example 2-2

[0079] The configuration of this embodiment is the same as that of embodiment 1, except that the stretching ratio is different, as shown in Table 10.

[0080] Table 10: Effect of different drawing ratios on fiber properties

[0081] Stretch ratio Breaking strength / N Breaking strength / cN / dtex Elongation at break / % Wire breakage 5.4 84.5 7.49 15.1 0 5.6 88.9 7.9 14.1 0 5.8 91.9 8.15 13.1 0 6.0 93.8 8.32 11.7 1 6.2 97.3 8.64 11.49 2 .

[0082] It can be seen from Table 10 that when the stretch ratio is 5.4-5.9, the spinning condition is good, and with the increase of the stretch ratio, the breaking strength and breaking strength gradually increase, while the breaking elongation gradually decreases; but when the stretch ratio exceeds 6.0, the breaking strength and breaking strength continue to increase, and sporadic wire breakage will occur; and when the stretch ratio exceeds 6.2, continuous wire breakage will occur. Based on the spinning condition requirements, it is appropriate to control the stretch ratio at 5.4-6.0.

[0083] The above-mentioned Examples 1 and 2 confirm that the stretching ratio has the same influence trend on different multifunctional polyester fibers: the breaking strength and breaking tenacity increase with the increasing stretching ratio, while the breaking elongation decreases with the increasing stretching ratio.

[0084] Example 3

[0085] This example prepares antistatic fluorescent functional polyester fibers as follows:

[0086] (1) Raw materials: white polyester chips are polyester chips with an intrinsic viscosity of 1.05 dl / g and a moisture content of 10 ppm; the first functional chips are antistatic masterbatch (an antistatic agent with polyether ester as a carrier), with an intrinsic viscosity of 0.63 dl / g and a moisture content of 10 ppm, and the addition amount is 10% of the mass of the white polyester chips; the second functional chips are fluorescent masterbatch (whitening agent PS-1 can be used in this embodiment), with an intrinsic viscosity of 0.50 dl / g, and the addition amount relative to the white polyester chips is 200 ppm.

[0087] (2) Feeding: Combined Figure 1 The white polyester chips are fed into the mixing bin 4 through the main bin 1, and the feeding speed of the white polyester chips is 83 kg / h; the first functional chips are fed into the mixing bin 4 through the sub-bin 1 2, and the second functional chips are fed into the small screw 8 through the sub-bin 2 3.

[0088] (3) Melt extrusion: the mixed material in the mixing bin 4 is fed into the main screw 5, and the parameters of the main screw 5 are set to 266°C / 285°C / 275°C / 268°C / 260°C / 265°C, 155 bar; the parameters of the small screw are set to 256°C / 276°C / 251°C / 240°C / 235°C, 75 bar, output 45%, metering pump speed 12.6 rpm, and drying temperature 132°C.

[0089] (4) Spinning:

[0090] Antistatic fluorescent polyester fiber with a specification of 1110dtex / 192f is spun, the spinneret specification is 0.6mm*1.2mm / 192f, and the filter element is 40μm sintered metal mesh.

[0091] GR-1+2: 442m / min;

[0092] GR-3+4: 488m / min, 91℃;

[0093] GR-5+6: 1750m / min, 133℃;

[0094] GR-7+8: 2461m / min, 232℃;

[0095] GR-9+10: 2386m / min, 132℃;

[0096] The stretch ratio was 5.4.

[0097] Before the winding process, a signal feedback device is set to detect the change of volume resistivity (YG321 fiber resistivity meter, tested by Changzhou Textile Instrument Factory) and color difference (or whiteness): to control the addition speed and amount of the first functional masterbatch (mainly to control white polyester chips) and the second functional masterbatch.

[0098] The breaking strength of the finished fiber is 93.6N, the breaking strength is 8.43cN / dtex, the breaking elongation is 12.6%, and the volume resistivity is 5.8×10 10 Ω·cm, ash absorption height <0.5cm.

[0099] Example 3-1:

[0100] The configuration of this embodiment is the same as that of embodiment 3, except that the amount of antistatic masterbatch added (relative mass ratio of white polyester chips) is different, so as to verify the effect of antistatic masterbatch on fiber properties, as shown in Table 11.

[0101] Table 11: Effect of different antistatic masterbatches on the proportion of white polyester chips

[0102]

[0103] It can be seen from Table 11 that the antistatic masterbatch has little effect on the mechanical properties of the fiber. The volume resistivity and dust absorption height of the fiber decrease with the increase of the addition amount of the antistatic masterbatch. When the addition ratio of the antistatic masterbatch is greater than 10%, the volume resistivity of the fiber reaches 10 10 Ω·cm (T=20℃, RH=65%), and almost no dust absorption (T=25℃, RH=40%). Therefore, it is appropriate to control the addition amount of antistatic masterbatch to 10-14% of the mass of white polyester chips.

[0104] Example 4

[0105] This embodiment is to prepare anti-ultraviolet and antibacterial functional polyester fibers, specifically as follows:

[0106] (1) Raw materials: White polyester chips are polyester chips with an intrinsic viscosity of 1.05 dl / g and a moisture content of 10 ppm; the first functional chips are anti-ultraviolet masterbatch (nano-TiO2), with an intrinsic viscosity of 0.48 dl / g and a moisture content of 20 ppm, and the addition amount is 200 ppm of the mass of the white polyester chips; the second functional chips are antibacterial masterbatch (nano-silver antibacterial agent can be used in this embodiment), with an intrinsic viscosity of 0.52 dl / g, and the addition amount relative to the white polyester chips is 100 ppm.

[0107] (2) Feeding: Combined Figure 1 The white polyester chips are fed into the mixing bin 4 through the main bin 1, and the feeding speed of the white polyester chips is 83 kg / h; the first functional chips are fed into the mixing bin 4 through the sub-bin 1 2, and the second functional chips are fed into the small screw 8 through the sub-bin 2 3.

[0108] (3) Melt extrusion: the mixed material in the mixing bin 4 is fed into the main screw 5, and the parameters of the main screw 5 are set to 296°C / 305°C / 298°C / 290°C / 285°C / 282°C, 190 bar; the parameters of the small screw are set to 288°C / 293°C / 290°C / 289°C / 273°C, 65 bar, output 55%, metering pump speed 13.3 rpm, and drying temperature 156°C.

[0109] (4) Spinning:

[0110] Antistatic fluorescent polyester fiber with a specification of 1110dtex / 192f is spun, the spinneret specification is 0.6mm*1.2mm / 192f, and the filter element is 40μm sintered metal mesh.

[0111] GR-1+2: 460m / min;

[0112] GR-3+4: 495m / min, 93℃;

[0113] GR-5+6: 1850m / min, 143℃;

[0114] GR-7+8: 2721m / min, 242℃;

[0115] GR-9+10: 2688m / min, 129℃;

[0116] The stretch ratio is 5.84.

[0117] Before the packaging process, a signal feedback device for detecting the aging strength retention rate and the silver ion content (inductively coupled plasma emission spectrometry, ICP-OES) is set to control the adding speed and amount of the first functional masterbatch (mainly controlling the white polyester chips) and the second functional masterbatch.

[0118] The breaking strength of the finished fiber is 84.4N, the breaking strength is 7.6cN / dtex, the dry heat shrinkage is 6.0%, and the breaking elongation is 15.9%; the 300h artificial fluorescent ultraviolet lamp accelerated aging experiment shows that it has strong anti-ultraviolet performance and the breaking strength retention rate is above 90%; the bacterial activity value is <-1.0 (JISL-1902-1998), and there is no fungal growth (JISZ-2911).

[0119] Comparative Example 1

[0120] In this comparative example, multifunctional polyester fibers are prepared by melt mixing. The same white polyester chips, flame retardant masterbatch and color masterbatch as in Example 1 are used for production by melt mixing. The above three components are all made into a melt state, and then the melt of the flame retardant masterbatch and the melt of the color masterbatch are added to the melt of the white polyester chips by melt mixing and then spun. We found that: the pressure difference before and after the metering pump is large and fluctuates significantly, the spinning stability is poor, the fiber breakage phenomenon is significant, and the spinning is difficult to be stable.

[0121] Comparative Example 2

[0122] In this comparative example, multifunctional polyester fibers were prepared by masterbatch mixing. The same white polyester chips, flame retardant masterbatch and color masterbatch as in Example 1 were used for production by chip mixing. The flame retardant masterbatch and color masterbatch were mixed with the white polyester chips and extruded for melt spinning. We found that the color masterbatch and the flame retardant masterbatch had large differences in thermal properties. Uneven melting and insufficient melting were prone to occur during extrusion melting, the filter element was seriously clogged, and fiber molding was difficult.

Claims

1. A method for preparing an anti-ultraviolet and antibacterial multifunctional polyester fiber, characterized in that: (1) Raw materials: White polyester chips are polyester chips with an intrinsic viscosity of 1.05 dl / g and a moisture content of 10 ppm; the first functional chips are nano-TiO2 with an intrinsic viscosity of 0.48 dl / g and a moisture content of 20 ppm, and the addition amount is 200 ppm of the mass of the white polyester chips; the second functional chips are nano-silver antibacterial agents with an intrinsic viscosity of 0.52 dl / g and an addition amount relative to the white polyester chips of 100 ppm. (2) Feeding: White polyester chips are fed into the mixing bin through the main bin, and the feeding speed of white polyester chips is 83 kg / h; the first functional chips are fed into the mixing bin through the sub-bin 1, and the second functional chips are fed into the small screw through the sub-bin 2. (3) Melt extrusion: The mixed material in the mixing bin is fed into the main screw. The parameters of the main screw are set as follows: zone 1 temperature is 296 °C, zone 2 temperature is 305 °C, zone 3 temperature is 298 °C, zone 4 temperature is 290 °C, zone 5 temperature is 285 °C, zone 6 temperature is 282 °C, 190 bar; The parameters of the small screw are set as follows: zone 1 temperature is 288 °C, zone 2 temperature is 293 °C, zone 3 temperature is 290 °C, zone 4 temperature is 289 °C, zone 5 temperature is 273 °C, 65 bar, output 55%, metering pump speed is 13.3 rpm, drying temperature is 156 °C, (4) Spinning process: Spinning 1110 dtex / 192 f anti-ultraviolet and antibacterial polyester fibers, spinneret specifications 0.6 mm*1.2 mm / 192 f, 40 μm sintered metal mesh filter element, The temperature and speed of each spinning winding roller are set as follows: The roller speed of GR-1+2 is 460 m / min; The roller speed of GR-3+4 is 495 m / min and the roller temperature is 93 °C; The roller speed of GR-5+6 is 1850 m / min and the roller temperature is 143 °C; The roller speed of GR-7+8 is 2721 m / min and the roller temperature is 242 °C; The roller speed of GR-9+10 is 2688 m / min, and the roller temperature is 129 ℃. The stretch ratio is 5.84, Before the packaging process, a signal feedback device for detecting the aging strength retention rate and the silver ion content is set to control the adding speed and amount of the first functional slice and the second functional slice. The obtained anti-ultraviolet and antibacterial multifunctional polyester fiber has a breaking strength of 84.4 N, a breaking strength of 7.6 cN / dtex, a dry heat shrinkage of 6.0%, and an elongation at break of 15.9%; the 300-h artificial fluorescent ultraviolet lamp accelerated aging experiment shows that it has strong anti-ultraviolet performance and a breaking strength retention rate of more than 90%; the bacterial activity value is less than -1.0, and there is no fungal growth.

Citation Information

Patent Citations

  • Process for producing melt direct-spinning multifunctional PET (Polyester) industrial yarns

    CN102787376A

  • Functional slice mixing device

    CN214612856U

Cited By

  • Preparation system and method of antibacterial sharpened filaments

    CN120866955A